2022
DOI: 10.3389/fcvm.2022.947959
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine and coronary heart disease risks: A meta-analysis of randomized controlled clinical trials

Abstract: BackgroundSeveral trials have considered the safety and clinical benefits of colchicine as a treatment option for secondary prevention in patients with coronary atherosclerotic heart disease (CAD), but its safety and clinical benefits remain controversial. The purpose of this study was to explore the clinical benefits of colchicine, focusing on certain subgroups of patients.MethodsRandomized controlled trials (RCTs) of colchicine in subjects with acute or chronic CAD compared with controls were included to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Colchicine may be beneficial as an additional secondary prevention drug in patients post-ACS. Recent meta-analyses ( 139 142 ) have shown that colchicine positively reduces the incidence of MACE, MI, stroke, and revascularization and decreases cardiovascular events, inflammatory markers, hs-CRP, and IL-6 in patients with coronary artery disease. But with a higher incidence of gastrointestinal distress and no effect on all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Colchicine may be beneficial as an additional secondary prevention drug in patients post-ACS. Recent meta-analyses ( 139 142 ) have shown that colchicine positively reduces the incidence of MACE, MI, stroke, and revascularization and decreases cardiovascular events, inflammatory markers, hs-CRP, and IL-6 in patients with coronary artery disease. But with a higher incidence of gastrointestinal distress and no effect on all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“… 66 , 67 Nevertheless, such benefits were not attributed to a mortality benefit in this network meta-analysis, which was consistent with the findings of previous meta-analyses. 20 , 63 , 68 It should not be ignored that various disease types were evaluated in eligible studies, therefore inevitably introducing bias to compromise mortality benefit. Moreover, we cannot also eliminate the influence of variations in follow-up durations on mortality.…”
Section: Discussionmentioning
confidence: 99%
“…To date, many conventional pairwise meta-analyses have systematically evaluated and consistently established the effects and safety of colchicine for the treatment of patients with CAD [19][20][21][22][23][24][25][26]63,68,69 ; however, all these findings from previous meta-analyses did not inform practitioners which dosing regimen may be preferred for these patients. Given this open issue, the current network meta-analysis rationally classified colchicine dose into 3 regimens based on published evidence 26 and first determined the comparative efficacy and safety among 3 dosing regimens.…”
Section: The Strengths Of This Network Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A number of meta-analyses have demonstrated the positive effects of LoDoCo on the prognosis of patients with coronary heart disease, such as a significant reduction in cardiovascular mortality, myocardial infarction, and stroke ( Samuel et al, 2021a ; Samuel et al, 2021b ; Xia et al, 2021 ; Ma et al, 2022 ). The systematic review by Samuel et al also supported this result ( Fiolet et al, 2021 ).…”
Section: Use Of Colchicine In Cardiovascular Diseasementioning
confidence: 99%